Influence of organizational and project practices on design error costs - Love, Peter; Lopez, Robert; Kim, J.; Kim, M. (American Society of Civil Engineers, 2014)
The organizational and project-related practices adopted by design firms can influence the nature and ability of people to perform their tasks. In recognition of such influences, a structured survey questionnaire was used to determine the key factors contributing to design error costs in 139 Australian construction projects. Using stepwise multiple regressions, the significant organizational and project-related variables influencing design error costs are determined. The analysis revealed that the mean design error costs for the sample projects were 14.2% of the original contract value. Significant organizational and project factors influencing design error included inadequate training for employees and unrealistic design and documentation schedules required by clients. From the findings, key strategies for reducing design errors that are attributable to organization and project-related practices are identified